The Role of Women in the Conflict in Cabo Delgado: Understanding Vicious Cycles of Violence - Feijó, João (Rural Observer, 2021)
Since October 2017, Cabo Delgado Province has been an arena of armed conflict, translating into destruction and looting, abductions and killings of civilian populations. The conflict intensified throughout 2020, with attacks on district headquarters villages, leading to the forced displacement of hundreds of thousands of individuals. The history of armed conflicts in Mozambique shows that they have had enormous impacts on the civilian population, placed between two opposing groups: rebel forces and government forces. Aware of their respective importance in a guerrilla war (for the possibility of logistical support, camouflage, recruitment, or the provision of information), the warring parties have always related to the civilian population on the basis of mistrust, imposing their domination by force and persuasion, and seeking to interfere in their habitat (in clusters or scattered in the bush). Being physically more fragile, target for sexual predation by armed young men, and traditionally a food producer, women were a recurrent target, remaining in a particularly vulnerable position. In the current armed conflict in northeast Cabo Delgado, there have been numerous reports of abduction of hundreds of young women, and there is much doubt about their whereabouts. However, viewing women only as passive victims of the conflict does not capture the complexity of the situation. Voluntarily or forcibly, by conviction or without choice, the literature shows that women play an active role in armed conflicts, as observers and providers of military information, in providing logistical support, as vigilantes, and even as soldiers. This active involvement of women is all the more evident the larger the social support base of the insurgent groups. This study aims to portray the impact of the armed conflict on women during the armed conflict in northern Cabo Delgado, analyzing not only the wide range of violence committed against them, but also the forms of collaboration (more or less voluntary) with rebel groups and their organizational dynamics.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; gender / género; ⛔ No DOI found

Displacement Tracking Matrix - Mozambique Ett Report: No. 54/ 27 March - 26 April 2021 17:00h Emergency tracking tool (ett) - IOM - International Organisation for Migration (IOM, 2021)
Following the recent attacks in Palma Sede, DTM teams in Nangade, Mueda, Montepuez, and Pemba districts continue to register significant rise in IDP arrivals since 27 March. On 26 April 2021, an estimated number of 1,118 IDPs were registered in the four districts bringing the total number of IDPs to 27,913 people who have been displaced from Palma. IDPs continue to arrive in Nangade on foot and by bus from Nangade to Mueda, Montepuez, and Pemba.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Displacement Tracking Matrix - Mozambique Ett Report: No. 54/ 27 March - 15 April 2021 17:00h Emergency tracking tool (ett) - IOM - International Organisation for Migration (ETT, 2021)
Following the recent attacks in Palma Sede, DTM teams in Nangade, Mueda, Montpuez, and Pemba districts continue to register significant rise in IDP arrivals since 27 March. On 15 April 2021, an estimated number of 1,260 IDPs were registered in the four districts bringing the total number of IDPs to 19,921 people who have been displaced from Palma. IDPs continue to arrive in Nangade on foot and by bus from Nangade to Mueda, Montepuez, and Pemba.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Cabo Ligado (Mozambique Conflict Observatory ) Cabo Ligado Weekly: 1-7 March - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; private sector / setor privado

Cabo Ligado 39 - ACLED (ACLED, 2021)
On 22 February, insurgents conducted two attacks along the border between Nangade and Mocimboa da Praia districts. The first, a morning attack, took place at Ingalonga, Nangade district. Insurgents beheaded two people there. Later that day, across the border in Mitope, Mocimboa da Praia district, insurgents captured three women and three men who had been working in their fields. One woman was released, and the three men were beheaded. Local militias deployed to the area in response, but no clashes were reported. Three days later insurgents struck closer to the Nangade district capital, attacking the village of Luneque, which is only 10 kilometers from Nangade town. The attackers killed four civilians in the town, and caused many others to flee to the district capital. On the evening of 26 February, insurgents surprised residents of Quirinde, Palma district as they ate dinner. Residents fled, but insurgents killed seven, three of whom were beheaded. Insurgents also destroyed homes and looted food and other goods. Quirinde is a coastal village north of Palma town, about six kilometers east of Quionga, which insurgents attacked on 19 February. One source reports that helicopters belonging to government forces or government contractors pursued the Quirinde attackers, causing an indeterminate number of casualties. According to Pinnacle News, the government has deployed two battalions of the police Rapid Intervention Unit to the area in an attempt to prevent further insurgent attacks on the route between Palma and the Tanzanian border.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Mozambique - Emergency Tracking Tool - Palma Crisis Report - 50 (27 March - 10 April 2021) - IOM - International Organisation for Migration (IOM, 2021)
Following the recent attacks in Palma Sede, DTM teams in Nangade, Mueda, Montpuez, and Pemba districts continue to register significant rise in IDP arrivals since 27 March. On 10 April 2021, an estimated number of 603 were registered in the four districts bringing the total number of IDPs to 15,179 People who have been displaced from Palma continue to arrive in Nangade on foot and by bus from Nangade to Mueda, Montepuez, and Pemba.
Keywords: G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

UNHCR Mozambique IDP Response External Update 2-15 April.pdf - UNHCR (UNHCR - The UN Refugee Agency, 2021)
As of 15 April, over 20,0001 people from Palma are forcibly displaced, in the aftermath of Non-State Armed Group (NSAG) attacks on 24 March. They fled to the districts of Nangade, Mueda, Montepuez and Pemba by land, foot, air and sea. This is in addition to the nearly 700,000 already displaced in the provinces of Cabo Delgado, Nampula, Niassa, Sofala and Zambezia as a result of violence and insecurity in Cabo Delgado. UNHCR received reports that several families from Palma attempted to seek asylum in Tanzania due to the proximity to the border and were forcibly returned to Mozambique.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; accountability / responsabilização; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

The Mozambique Conflict and Deteriorating Security Situation - Bukarti, Bulama; Munasinghe, Sandun (Tony Blair Institute for Global Change, 2020)
For almost three years, the ISIS-affiliated extremist group Ansar al-Sunna has spearheaded an insurgency in Mozambique’s northern province of Cabo Delgado. In recent months the situation in Cabo Delgado has deteriorated significantly and violent attacks are now frequent. Militants have begun to target military positions having previously focused on civilian targets. It is a sign that the group is growing in resilience, operational capacity and confidence. From its first few attacks in Mocimboa de Praia in late 2017, the group now launches more than 20 attacks every month in an insurgency that covers nine major towns and districts along the Cabo Delgado coast. A battle for the town of Macomia at the end of May demonstrates the group’s organisational capacity and ambition as well as an escalation in the government’s counter-offensive efforts. On 30 May 2020, government forces engaged Ansar al-Sunna militants in one of the largest counter-terrorism operations to date, resulting in the reported deaths of 78 insurgents, including two of the group’s leaders. The extent to which this will impact Ansar al-Sunna’s operations and long-term ambitions remains to be understood.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; youth / juventude

War in resource-rich northern Mozambique – six scenarios 2020.pdf - Santos, F. A. dos (Chr. Michelsen Institute, 2020)
Since the October 2017 attacks by alleged Islamist insurgents, commonly referred to as Ahlu Sunnah Wa-Jama and locally know as Al Shabab, on Mocimboa da Praia, it has not been entirely clear who the attackers were, what their strategic objectives are and on whose domestic and international support they rely. This paper, grounded in a historical understanding of conflict in northern Mozambique’s Cabo Delgado Province, seeks to identify possible stakeholders and scenarios in what we no longer see as an insurgency, but a war.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Social asymmetries: clues to understand the spread of islamist jihadism in Cabo Delgado - Feijó, João, Friedrich-Ebert-Stiftung, Peace and Security Centre of Competence Sub-Saharan Africa (Friedrich-Ebert-Stiftung Peace and Security, 2020)
This article intends to reflect around the level of poverty and inequality existing among the various ethno-linguistic groups of the province, trying to gauge the extent to which they may be at the root of the current conflict. In this sense, 94 individuals were interviewed in the districts of Palma, Mocímboa da Praia, Macomia, Muidumbe and Montepuez (macuas, macondes, muânis and mácues), trying to understand what representations they build on the different ethno-linguistic groups in the province, in terms of access to business, employment and income, as well as State support. Throughout the text, an attempt is made to understand the socio-economic factors that can lead to the adherence (direct or indirect) of local populations to violent groups.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; poverty / pobreza

Mozambique: Military maritime cooperation agreement with France under discussion - Lusa (Club of Mozambique, 2020)
Mozambique and France are discussing a military maritime cooperation agreement, a diplomatic source in the European country told Lusa in the context of possible support in the fight against terrorism in Cabo Delgado. "No operational military support has been provided to Cabo Delgado by the French
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; GP - Cabo Delgado; L - english / inglês; conflict / conflito

Walking the talk?: A critical perspective on sustainable peace and reconciliation in Mozambique - Weimer, Bernhard (Friedrich-Ebert-Stiftung, Peace and Security Centre of Competence Sub-Saharan Africa, 2020)
The August 2019 Maputo Accord on Peace and Reconciliation appears not to be standing on entirely solid ground. Not only has the decentralization agreement suffered from last minute ‘adulteration’, but also the DDR process has been lacking speed and rigour. The circumstances and outcomes of the October 2019 elections have cast doubt on the extent to which Renamo will abide to the August 2019 agreement. The party appears to be split on the matter of the – officially disowned armed Junta Militar maintaining low-intensity, nevertheless deadly, attacks on civilian traffic in central Mozambique. Thus it remains doubtful at the beginning of 2020 to what extent the ambitious DDR process, the key Pillar/Provision of the most recent peace agreement, may be implemented and by when. Further, the institutional setup of the Peace Secretariat and the donor-financed MDTF for DDR process leave doubts about national ownership of and responsibility for the implementation of the Peace Agreement, which uses reconciliation as a token, but avoids getting to its substance. Apart from these factors, the summary amnesty legislation benefitting both former warring parties prevents the possibility of publicly discussing justice and pursuing war crimes. With Frelimo’s impressive, albeit amply contested, win of the 2019 elections at the national level and provincial tier of government, the paradigm of ‘winner takes all’ may come back into political reality, which in the past had triggered armed conflict and prompted political negotiations on some degree of power sharing through decentralization arrangements. In some senior political circles, this paradigm is now paraphrased as the introduction of a benevolent authoritarian African regime, at the cost of democratic checks and balances and a strong civil society. Under these circumstances, reconciliation initiatives as sketched above , primarily promoted by civil society in the broadest sense and including FBOs, would seem a viable strategy to breathe new life into the August 2019 agreement and opening space for the youth to actively engage the political parties which, up to today, they had talked peace but remained prepared for war. Only Chissano, in the aftermath of the Rome General Peace Accord, attempted to ‘walk the reconciliation talk’. The present constellation and the terrible consequences for lives and livelihoods in Cabo Delgado would also represent a strategic opportunity to become actively involved in peace consolidation, from which the Mozambican CSOs have been kept at a distance, leaving peace-making to political leaders only. A Malawian proverb suggests that he who thinks he is leading but has no followers is only taking a walk.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; conflict - civil war / conflito - guerra civil; conflict / conflito

Conflict at a Crossroads: Northern Mozambique at a Crossroads - Devermont, Judd; Columbo, Emilia (Northern Mozambique at a Crossroads, 2019)
On October 5, 2017, a group of armed men attacked three police stations in Moçimboa da Praia, starting nearly two years of violence and insecurity that still show no sign of ending. Between the first October incident and August 27, 2019, extremists conducted 173 attacks—79 percent of which were committed against civilians—resulting in over 350 deaths, according to the Armed Conflict Location and Event Database (ACLED).1 There is no consensus on the name or construct of the group committing the violence, but for the purposes of this paper, we will refer to the group as Ahlu Sunnah Wa-Jama (ASWJ), which is one of the several names that observers and local communities have ascribed to the militants.2
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito; youth / juventude

Islamic Insurgency in Cabo Delgado: Extractive Industry, Youth Revolt and Global Terrorism in Northern Mozambique - Bonate, Liazzat J. K. (The University of the West Indies, St Augustine, 2018)
The violent insurgency in northern Mozambican province of Cabo Delgado, that started in October 2017 and is still ongoing, caught the government of the country and the public by surprise. Although this insurgency remains largely unexplored and little understood, the only study done so far has suggested that it is being carried out by Muslim youth connected to Islamic radicalism, in particular to the Harakat alShabaab of Somalia and its offshoots in Kenya, Tanzania, and as far as DRC.1 Islam has a long history in Mozambique, since probably the eighth century.2 According to the 2017 National Population Census, Muslims account for about 18% of the total population the country and 58% of the Cabo Delgado inhabitants. However, Mozambique had never had any visible Islamist radical political movement before.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; youth / juventude

Mozambique’s insurgency: a new Boko Haram or youth demanding an end to marginalisation? - Hanlon, Joseph (Africa at LSE, 2018)
Joseph Hanlon argues that Mozambique’s new “Islamic” insurgency is about marginalised youth demanding to be heard, and therefore is similar to anti-establishment protest across the world.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Mozambique: A Political Economy Analysis - Orre, Aslak; Rønning, Helge (NUPI political economy reports, 2017)
This report uses a political economy analysis to shed light on some of the paradoxes that characterise Mozambique mid 2017: Entrenched poverty, the resuscitated armed conflict/war, the trust crisis between the Mozambican (Frelimo) government and its development partners, the spiralling debt and the party-state.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; conflict / conflito; poverty / pobreza

Power and Participation in Rural Development: A Case Study from Mozambique - Valderrama, Camilo Eduardo (Institute of Development Studies, University of Sussex, 2009)
This study on power and participation in post-conflict settings analyzes a rural development project in Mandimba District of Northern Mozambique. The purpose is to gain understanding of the dynamics and possibilities of participatory approaches for increasing the influence of previously excluded actors in decision-making processes. The methodology for this study reflects two broad yet intertwined approaches. For the first component, the Mozambique in-depth case study research, I draw on my role as a participant observer as well as other more traditional field research approaches. A variety of qualitative methods were used for the collection of the information, including review of documentary sources, participant observation, key informant and focus group interviews. The initial data collection lasted about eight months in different phases between 1998 and 1999. In Mozambique, but also in subsequent years, my approach drew upon principles of reflective practice, where I learned not only through the study of others, but through reflections on my work as a practitioner in conflict areas being studied. This latter approach was particularly important when triangulating and extending the findings from the Mozambique study to other war-torn settings in which I later worked in Kosovo, Pakistan and Chad and when reviewing documented experiences in participatory processes in Afghanistan and East Timor. A 'power over' and 'actor oriented' approach informed data collection and analysis of the information. The findings show that inclusive participatory approaches may fail if they do not address power. They may sideline power asymmetries and fail to set rules of involvement for actors within the project. In addition, structural and functional factors related to the project frame can enhance or constrain participation. The finding also shows that the inflexibility of the project frame constrains actor engagement in decision-making processes. The theoretical implication of this research calls for an approach to power rooted in the mix of conflict and consensual understanding of power. Practical implications point towards a greater emphasis on 'decision ruling', i.e. setting the 'rules of the game' for decision-making in participatory processes.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mandimba; GP - Niassa; L - english / inglês; citizenship & participation / cidadania e participação; conflict - civil war / conflito - guerra civil; conflict / conflito; power / poder; rural development / desenvolvimento rural

'Dhlakama É Maningue Nice!': An Atypical Former Guerrilla in the Mozambican Electoral Campaign - Cahen, M. (Transformation, 1998)
Despite significant problems with urban criminal gangs and highway robbers, Mozambique is a country at peace since 4 October, 1992. Under the auspices of the Italian religious congregation of Santo Egidio,4 Joaquim Alberto Chissano, president of the Republic and of the Frente de libertagao de Mozambique (FRELIMO), once the 'Marxist-Leninist' single-party of the country, and Afonso Dhlakama, president of the Resistencia national de Mogambique (RENAMO), the former guerrilla group and longtime recipient of aid from South Africa, signed the 'General Peace Accord' on that date. This agreement has never seriously been called into question. During the first 15 days following the accord there were a number of incidents. For example, it contained provisions for maintaining each party's administration in their part of the country, but did not specify the zones belonging to one party or the other. As a result, a number of RENAMO regional commanders sought to occupy areas that they had not previously controlled, the largest one being Angoche in Zambezia. It appears that they had told Afonso Dhlakama that they already held these areas, and following the peace accords, they urgently sought to gain real possession of the territory in question.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; conflict / conflito; ⛔ No DOI found

Islamic Radicalization in Northern Mozambique: The Case of Mocímboa da Praia - Habibe, Saide; Forquilha, Salvador; Pereira, João (Cadernos IESE)
Este artigo analisa o fenómeno da radicalização islâmica no Norte de Moçambique, explorando a complexidade das dinâmicas não só na origem do grupo dos Al-Shabaab como também na estrutura do próprio conflito e violência em Cabo Delgado. Os autores consideram que o fenómeno exige uma pesquisa multidisciplinar aprofundada que tome em conta uma multiplicidade de factores de ordem histórica, social, política, económica e religiosa. Acesso à versão inglesa aqui. ----- This research report is a first attempt to address the phenomenon in order to understand the complexity of the dynamics not only in the origin of the Al-Shabaab group but also in the structure of the conflict and violence in Cabo Delgado. Almost two years after the first attack on Mocímboa da Praia (5 October 2017), the phenomenon has been the subject of multiple interpretations, from the (at least public) Mozambican government’s preferred thesis of a conspiracy driven by external forces opposed to Mozambique’s development, through the land conflict against the backdrop of the area’s natural resources thesis, to the sect (Morier-Genoud, 2019) and jihadism theses, in the context of the growing dynamics of violent extremism in the countries of the region i.e. Tanzania, Kenya and the Great Lakes region. While highlighting this last thesis (jihadism), our exploratory research has shown that the phenomenon is complex and requires profound multidisciplinary research that takes into account a multiplicity of historical, social, political, economic and religious factors. This is why, rather than draw conclusions, this report ends with a series of questions: • Why is Mocímboa da Praia the epicentre of the phenomenon? • How does the Mozambican state deal with the proliferation of religious institutions in the country? • What are the implications of the Islamic radicalization phenomenon for investments in the country’s northern region? To what extent can these investments heighten or reduce local cleavages and contribute to Islamic radicalization phenomenon? • To what extent does the Islamic radicalization phenomenon affect current efforts to stabilize the country politically and economically? • To what extent can regional dynamics (Tanzania, Kenya, Great Lakes region) influence the evolution of the phenomenon in Mozambique? • What kind of policies (including security) does the country need to address the phenomenon? • What lessons does the phenomenon bring to the state-building process in Mozambique? These questions feed into the ongoing research program at the Institute for Social and Economic Studies (IESE) since early 2019, involving researchers from IESE and other research centres, entitled “State, Violence and Development Challenges in Cabo Delgado”.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; poverty / pobreza; youth / juventude